2022
DOI: 10.1186/s13059-022-02651-9
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the multicellular ecosystem of vena caval tumor thrombus in clear cell renal cell carcinoma by single-cell RNA sequencing

Abstract: Background Vascular invasion with tumor thrombus frequently occurs in advanced renal cell carcinoma (RCC). Thrombectomy is one of the most challenging surgeries with high rate of perioperative morbidity and mortality. However, the mechanisms driving tumor thrombus formation are poorly understood which is required for designing effective therapy for eliminating tumor thrombus. Results We perform single-cell RNA sequencing analysis of 19 surgical tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 102 publications
1
27
0
Order By: Relevance
“…Here, a single-cell transcriptomics study in locally invasive ccRCC identified CAFmediated extracellular matrix remodeling by the increased gene signature for the EMT pathway (29). Therefore, in both recurrent and locally invasive ccRCC, CAF infiltrate should be considered as an additional key cell type driving tumor progression and immunosuppression (29,73). Stromal cells in recurrent and locally invasive ccRCC.…”
Section: Cancer-associated Fibroblasts In Recurrent and Locally Invas...mentioning
confidence: 93%
See 3 more Smart Citations
“…Here, a single-cell transcriptomics study in locally invasive ccRCC identified CAFmediated extracellular matrix remodeling by the increased gene signature for the EMT pathway (29). Therefore, in both recurrent and locally invasive ccRCC, CAF infiltrate should be considered as an additional key cell type driving tumor progression and immunosuppression (29,73). Stromal cells in recurrent and locally invasive ccRCC.…”
Section: Cancer-associated Fibroblasts In Recurrent and Locally Invas...mentioning
confidence: 93%
“…Interestingly, CAF mediated EMT has been proposed within locally invasive ccRCC that rapidly extends into surrounding large vessels (Figure 3). Here, a single-cell transcriptomics study in locally invasive ccRCC identified CAFmediated extracellular matrix remodeling by the increased gene signature for the EMT pathway (29). Therefore, in both recurrent and locally invasive ccRCC, CAF infiltrate should be considered as an additional key cell type driving tumor progression and immunosuppression (29,73).…”
Section: Cancer-associated Fibroblasts In Recurrent and Locally Invas...mentioning
confidence: 94%
See 2 more Smart Citations
“…It results in possibly misleading and truly heterogeneous findings on 5-year overall survival (OS) of patients with RCC and coexisting tumor thrombus that is reported to be from 34% to 71% (2)(3)(4)(5). Recently, some novel promising factors have emerged besides classic clinicopathological features, but also blood countderived biomarkers, and immunohistochemical and genetic signatures (6)(7)(8).…”
mentioning
confidence: 99%